Hersch Lauterpacht: Some Reminiscences - Barton, George (Victoria University of Wellington Law Review, 2012)
We end this valedictory volume with some reminiscences by Dr George Barton QC himself. They were written at the request of Sir Elihu Lauterpacht at the time he was preparing the book E Lauterpacht The Life of Hersch Lauterpacht (University of Cambridge, United Kingdom, 2010).